1994
DOI: 10.1063/1.868363
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphosis of a hairpin vortex into a young turbulent spot

Abstract: Direct numerical simulation was used to study the formation and growth of a hairpin vortex in a at-plate boundary layer and its later development i n to a young turbulent spot. Fluid injection through a slit in the wall triggered the initial vortex. The legs of the vortex were stretched into a hairpin shape as it traveled downstream. Multiple hairpin vortex heads developed between the stretched legs. New vortices formed beneath the streamwise-elongated vortex legs. The continued development of additional vorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 25 publications
9
69
0
Order By: Relevance
“…"Vortex Breakdown" has been widely spread in many research papers and textbooks [5,[9][10][11]. However, our analysis found that "Vortex Breakdown" is theoretically impossible.…”
Section: Vortexmentioning
confidence: 44%
See 2 more Smart Citations
“…"Vortex Breakdown" has been widely spread in many research papers and textbooks [5,[9][10][11]. However, our analysis found that "Vortex Breakdown" is theoretically impossible.…”
Section: Vortexmentioning
confidence: 44%
“…In practice, "Vortex Breakdown" can never happen. It is found that "Vortex Breakdown" described by exiting publications [5,9,10] is either misinterpreted by 2D visualization or by using the pressure center as the vortex center.…”
Section: Vortexmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustained efforts have been devoted to study properties and dynamics of transitional-turbulent spots (TRTSs) in the natural or bypass transitions of the ZPGSFPBL (18)(19)(20)(21)(22). It was long hoped that information extracted from TRTS during the inception of boundary-layer turbulence might shed light on the inner-layer dynamics, transport processes, and turbulence regeneration of the fully turbulent ZPGSFPBL.…”
mentioning
confidence: 99%
“…Robinson [2] confirmed the existence of non-symmetric archand quasi-streamwise vortices on the basis of the evaluation of DNS results. Studies involving the dynamics of hairpin vortices in the boundary layer have been performed by Perry & Chong [3], Acarlar & Smith [4,5], Smith et al [6], Haidari & Smith [7] and Singer & Joslin [8]. On these bases, a picture of vortex generation and reciprocal interaction in the boundary layer emerges in which processes of interaction of existing vortices with wall-layer fluid involve viscous-inviscid interaction, generation of new vorticity, redistribution of existing vorticity, vortex stretching near the wall and vortex relaxation in the outer region.…”
Section: Introductionmentioning
confidence: 99%